Is there evidence of bradykinesia in essential tremor?. (31st May 2020) - Bologna, M.; Paparella, G.; Colella, D.; Cannavacciuolo, A.; Angelini, L.; Alunni‐Fegatelli, D.; Guerra, A.; Berardelli, A.
Abstract : Background and purpose: Essential tremor (ET) is a movement disorder primarily characterized by upper limb postural and kinetic tremor. Although still under‐investigated, bradykinesia may be part of the phenotypic spectrum of ET. The aim was to evaluate bradykinesia features in ET through clinical examination and kinematic analysis of repetitive finger movements. Data collected in ET patients were compared with those recorded in Parkinson's disease patients and healthy controls. Methods: Overall, 258 subjects participated in the study (90 ET patients, 84 Parkinson's disease patients and 84 healthy controls). Repetitive finger tapping was kinematically recorded using a motion analysis system. Movement velocity, amplitude and decrement (sequence effect) were measured. The three groups were first compared by one‐way analysis of variance. A cluster analysis was also performed to better address the data variability observed in ET patients. Possible relationships between kinematic and clinical data were assessed in ET patients. Results: Essential tremor patients were slower than healthy controls. Movement slowness in ET did not correlate with postural or kinetic tremor severity. It was also found that movement slowness in ET was not associated with a sequence effect, which instead is a common feature in Parkinson's disease. Cluster analysis showed that a proportion of ET patients may have movement abnormalities similar to those observed in Parkinson's disease. Conclusions: Movement slowness without sequence effect is a common feature in ET patients. The present findings are relevant when interpreted in the context of the new tremor classification system and in the development of a more accurate bradykinesia definition.